MENTAL HEALTH IMPACTS BY ELEVATED DIGITAL SCREEN TIME DURING COVID-19 PANDEMIC - Putera, Muhammad Delvin Ario (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – The length of time invested in and the various activities carried out utilizing digital devices are referred to as screen time. The COVID-19 pandemic's restrictions on social interactions exacerbated the overuse of digital gadgets for everyday tasks like socializing, education, shopping, working, meeting, and entertainment. Increased screen usage has been thought to have harmful impacts on psychiatric health in studies. Methods – Several journal articles were used as references, with the inclusion criteria of literature that discuss the mental health impacts of elevated digital screen time during the pandemic of COVID-19 and its recommended measures to minimize its adverse mental health outcomes and the promotion of healthy digital habits. Results – During the pandemic of COVID-19, the unprecedented digital life led to higher numbers of anxiety, sadness, confusion, and unpleasant feelings including irritation and violence. it is crucial to know how screen use time evolved during the COVID-19 period of crisis so that the design of health promotion and intervention may be planned and informed. This study aims to discuss the mental health impacts of elevated digital screen time on the pandemic of COVID-19 and strategies to minimize its adverse mental health outcomes, and the promotion of healthy digital habits. Discuss – Boosting collaborative research involving worldwide nations to tackle COVID-19-related public health concerns can improve global evidence and future policies. Increased screen usage has been displayed to have harmful impacts on psychiatric health in studies. Excessive digital use has been linked to attention deficit disorders, social and emotional cognitive impairment, social withdrawal, phantom vibration syndrome, and major psychiatric diseases such as depression, anxiety, and gaming addiction. Conclusion – It is critical to promote good digital practices and good applications of digital media to avoid the negative effects of increased screen time. To prevent hazardous screen usage and other behaviors that may influence the mental health and welfare of COVID-19-affected people, it is critical to harness the evidence available and adopt multimodal strategies. Keywords: mental health, screen time, COVID-19.